Trichoderma asperellum as a preventive and curative agent to control Fusarium wilt in Stevia rebaudiana (2021)
Stevia has been introduced in many countries for the production of sugar-free sweeteners. Concurrently, several emerging pathogens have been described in this plant host. One of the latest has been Fusarium oxysporum, a well-known soil-borne pathogen causing vascular wilt in many plants. Classical methods to control Fusarium wilt are being questioned, and biocontrol agents are gaining importance as part of integrated approaches to manage the disease. Different species of Trichoderma have been described as optimal candidates to control F. oxysporum. However, their effectiveness is generally reported in annual plants and efficacy depends on the application protocol. We conducted an experiment to assess the preventive or curative potential of the rhizospheric T. asperellum UDEAGIEM-H01 strain against F. oxysporum on rooted cuttings of S. rebaudiana. After 33 days, F. oxysporum-infected stevia seedlings were severely affected (90% of disease incidence). Contrastingly, only 10% of the T. asperellum pre-treated plants and 70% of the post-treated showed Fusarium wilt symptoms. Dual confrontation assays proved the potential antagonistic effect of T. asperellum against F. oxysporum and five additional soil-borne pathogens affecting S. rebaudiana. Further in vitro tests revealed that this new strain of T. asperellum produces phytohormones (salicylic and jasmonic acid), and the secretion of cell-wall degrading enzymes (chitinases and cellulases); this ability could be related to its antagonistic and mycoparasitic activity. The present work concluded that T. asperellum UDEAGIEM-H01 has a high ability, mainly as a preventive agent, to control F. oxysporum in stevia plants showing further antagonistic effects and mycoparasitism on other fungal pathogens. © 2021 Elsevier Inc.